2021
DOI: 10.1016/j.toxrep.2021.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Short-term whole body cigarette smoke exposure induces regional differences in cellular response in the mouse larynx

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(37 citation statements)
references
References 112 publications
(161 reference statements)
1
36
0
Order By: Relevance
“…Mainstream CS from Kentucky 3R4F reference cigarettes was generated using inExpose smoking equipment (SCIREQ, Montreal, QB, Canada), consistent with our previous studies [12][13][14] . Exposure conditions were per the Federal Trade Commission (FTC)/International Standard Organization (ISO) standards (ISO 1991).…”
Section: Cigarette Smoke Generationmentioning
confidence: 98%
See 4 more Smart Citations
“…Mainstream CS from Kentucky 3R4F reference cigarettes was generated using inExpose smoking equipment (SCIREQ, Montreal, QB, Canada), consistent with our previous studies [12][13][14] . Exposure conditions were per the Federal Trade Commission (FTC)/International Standard Organization (ISO) standards (ISO 1991).…”
Section: Cigarette Smoke Generationmentioning
confidence: 98%
“…HD mice were exposed to 4 h of CS per day in 1-1.5 h increments, with room air breaks. Earlier studies in the airways and speci cally in the larynx, have shown that 1-4 h/day of CSE is su cient to induce histopathological changes 12,13,77,78 . LD and HD CS exposures were performed for 5 days/week, M-F for a total of 4 weeks as per the subacute inhalation toxicity guidelines regulated by the Organization for Economic Co-operation and Development (OECD) 79 .…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations